Decision-making in international entrepreneurship : unveiling cognitive implications towards entrepreneurial internationalisation - Jafari-Sadeghi, Vahid; Mahdiraji, Hannan Amoozad (Entrepreneurial behaviour series., 2023)
When it comes to international operations of entrepreneurial ventures, more clarification is needed to explore how, why, and under what conditions Small and Mid-size Enterprises (SME's) decide to take the risk of expanding internationally. This collection of studies presents an understanding of the processes, methods, and approaches towards decision-making in international entrepreneurship. Decision-Making in International Entrepreneurship provides comprehensive insight into what drives small and medium firms to internationalize entrepreneurially. Stressing multidisciplinary methods that support entrepreneurs in their internationalisation decision, the chapters analyse a broad range of statistical methods - regressions, panel data, structural equational modelling - as well as decision-making and optimisation models in both certain and uncertain circumstances. Decision-Making in International Entrepreneurship is essential reading for researchers, scholars, and practitioners looking to synthesise the process of decision-making towards exploiting entrepreneurial opportunities across national borders.